Diversity and Abundance of Waterbird Communities in the Jaffna and Kilinochchi Districts: Where do we have to go from here? - Kandasamy, G.; Weerakoon, D. K.; Sivaruban, A.; Jayasiri, H. B. (Faculty of Science, University of Jaffna, 2019)
Wetlands and waterbirds are inseparable elements. The preliminary study was conducted in eight sites, namely Mandaitivu, Mankumban, Kayts, Kavutharimunai, Pallai, Thadduvankoddy, Kapputhu and Nagarkovil in the Jaffna and Kilinochchi Districts of the northern region of Sri Lanka to determine the diversity and abundance of waterbirds. In each site, three counting blocks in length of 500 m with open width was selected for bird counting. Each block was separated at least by length of 500 m to avoid double counting. The counting of birds was done once a month from December, 2016 to May, 2017. Eighteen waterbird families were recorded. Phoenicopteridae, Anatidae and Scolopacidae were the dominant families. The presence of critically endangered species such as Spot-billed Duck (Anas poecilorhyncha) suggests the importance of conservation of these habitats. Two-way ANOVA indicated that waterbird families were significantly different among eight sites. The highest species richness was found in Kapputhu (57) and the lowest in Kavutharimunai (26). This study revealed that Mandaitivu, Mankumban, Kayts, Thadduvankoddy and Kapputhu are the excellent places to observe both migrant ducks and flamingos. Likewise Kavutharimunai is good for migrant shorebirds and seabirds by ferry while Nagarkovil and Kapputhu are suitable for viewing both feeding and roosting of waterbirds. On the whole this paper reveals that the northern region of Sri Lanka possess not only the potential of avitourism but also will become the hotspot of future bird researches, especially on waterbirds.
Keywords: Jaffna; Kilinochchi; Waterbird communities; Avitourism; Hotspot